Post Communist States in the World Community
XVII, 305 p.
Keywords: Post-Communist States in the World Community provides a selection of papers on various aspects of the foreign and security policies of the post-communist states of Europe presented originally at the Fifth World Congress of Central and East European Studies in Warsaw. The articles cover Russian foreign and security policy, Russian policy in Europe, the foreign policies of the countries of East-Central Europe and Russian policy in East Asia.